Spectrally Resolved White Light Interferometry for NaCl Aqueous Solutions Refractive Index Measurement - Likhachev, Igor G.; Pustovoy, Vladimir I.; Usievich, Boris A. (Frontiers in Physics, 2021)
In this work, a technique for comparing refractive indices for solutions of low concentrations has been developed. The method of direct spectral detection developed by the authors has been using. The solutions of low and ultra-low NaCl concentrations were compared with each other, as well as with the respective water controls. The solutions were prepared using the method of serial dilution with different types of mixing at each step: conventional stirring or intensive shaking. Measurements were made for water solutions of NaCl subjected to 6 to 12 and 30 hundredfold dilution, as well as for water controls, i.e. water subjected to the same technological procedure as the tested salt solutions.